2021
DOI: 10.1016/j.patter.2020.100169
|View full text |Cite
|
Sign up to set email alerts
|

Topic Modeling Uncovers Shifts in Media Framing of the German Renewable Energy Act

Abstract: Highlights d We assess coverage of the German Renewable Energy Act in newspapers over 18 years d Change-point analysis enables structural topic modeling to capture temporal dynamics d We introduce the notion of topic sentiment to assess the emotional content of topics d Positive accounts of the renewable industry shift to costs imposed on society

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 81 publications
(167 reference statements)
1
13
0
Order By: Relevance
“…The resulting topic classification was validated through qualitative examination of randomly selected documents from each of the top-20 topics. The same examination also showed that the topics were indeed corresponding to the theoretical concept of interest -that is, frames, -as we initially expected based on the previous research into other topic modeling techniques since our corpora were thematically focused from the beginning (Dehler-Holland et al, 2021;Maier et al, 2018). Additionally, based on the BERTopic results, we examined the evolution of topic frequency over time for the most popular topics.…”
Section: Data Analysis Rq1: Representation Of the War In Ukraine Thro...mentioning
confidence: 56%
“…The resulting topic classification was validated through qualitative examination of randomly selected documents from each of the top-20 topics. The same examination also showed that the topics were indeed corresponding to the theoretical concept of interest -that is, frames, -as we initially expected based on the previous research into other topic modeling techniques since our corpora were thematically focused from the beginning (Dehler-Holland et al, 2021;Maier et al, 2018). Additionally, based on the BERTopic results, we examined the evolution of topic frequency over time for the most popular topics.…”
Section: Data Analysis Rq1: Representation Of the War In Ukraine Thro...mentioning
confidence: 56%
“…In recent years, the need for a low-cost electricity supply has been repeatedly emphasized by politicians and the media [64,65], after the German electricity price had risen relatively sharply to one of the highest in Europe, partly due to the EEG levy [66,67]. Lauber and Jacobsson [68] criticize this increasingly dominant narrative, which is similarly described by Dehler-Holland et al and Schweiger et al [69,70]. By decision of the then liberal-conservative coalition, energy-intensive companies have been partially exempted from paying the EEG levy on their electricity consumption since 2012 [71], which increases the levy to be paid for all other consumers accordingly.…”
Section: Regimementioning
confidence: 99%
“…Ribeiro et al suggested the public perception assessment methodology to predict the public perception of renewable energy technologies using a regression model, and demonstrated its usefulness for hydro, wind, biomass, and solar energies in Portugal [9]. Dehler-Holland et al developed a structural topic model to perform sentiment analysis for the 6645 newspaper articles on German Renewable Energy Act [10].…”
Section: Ntanos Et Al Conducted a Survey To Understand The Greek Peop...mentioning
confidence: 99%